Exploring Determinants of Subjective Wellbeing in OECD Countries Evidence from the World Value Survey - Fleche, Sarah (OECD Publishing, 2012)
The paper explores issues with assessing wellbeing in OECD countries based on self-reported life satisfaction surveys in a pooled regression over time and countries, at the country level and the OECD average. The results, which are in line with previous studies of subjective wellbeing, show that, apart from income, the state of health, not being unemployed, and social relationships are particularly important for wellbeing with only some differences across countries. The results also show that cultural differences are not major drivers of differences in life satisfaction. Correlations between the rankings of measures of life satisfaction and other indicators of wellbeing such as the Human Development Index and Better Life Index are also relatively high. Measures of subjective wellbeing can play an important part in informing policy makers of progress with wellbeing in general, or what seems to matter for wellbeing- health, being employed and social contacts-- beyond income
Keywords: Social Issues/Migration/Health; Economics